Research and application of fuzzy logic to control the exhaust gas recirculation and fuel in dual fuel engines (LPG - DIESEL) - Nguyen , Van Long Giang; Do , Van Dung; Tran , Thanh Hai Tung; Duong , Trong Chung (Journal of Technical Education Science, 2016)
Research to reduce emissions from the engines diesel is very difficult mission, because the current emission standard is becoming very strictest NOx, HC, CO etc. Recently, dual fuel diesel engines which use Liquefied Petroleum Gas (LPG) and diesel fuel are being studied to control emissions and improve fuel efficiency. The research will propose using fuzzy logic to control the Diesel and LPG into the engine and diesel as a pilot fuel. Combined with the exhaust gas recirculation system (EGR) to reduce NOx levels in the exhaust. Both EGR and LPG are controlled by a fuzzy control system to improve the performance of the dual fuel engine.